Identification and Validation of Major QTLs, Epistatic Interactions, and Candidate Genes for Soybean Seed Shape and Weight Using Two Related RIL Populations - Elattar, Mahmoud A.; Karikari, Benjamin; Li, Shuguang; Song, Shiyu; Cao, Yongce; Aslam, Muhammed; Hina, Aiman; Abou-Elwafa, Salah Fatouh; Zhao, Tuanjie (Frontiers in Genetics, 2021)
Understanding the genetic mechanism underlying seed size, shape, and weight is essential for enhancing soybean cultivars. High-density genetic maps of two recombinant inbred line (RIL) populations, LM6 and ZM6, evaluated across multiple environments to identify and validate M-QTLs as well as identify candidate genes behind major and stable QTLs. A total of 239 and 43 M-QTLs were mapped by composite interval mapping (CIM) and mixed-model based composite interval mapping (MCIM) approaches, from which 180 and 18, respectively, are novel QTLs. Twenty-two QTLs including four novel major QTLs were validated in the two RIL populations across multiple environments. Moreover, 18 QTLs showed significant AE effects, and 40 pairwise of the identified QTLs exhibited digenic epistatic effects. Thirty-four QTLs associated with seed flatness index were identified and reported here for the first time. Seven QTL clusters comprise several QTLs for seed size, shape and weight on genomic regions of chromosomes 3, 4, 5, 7, 9, 17 and 19 were identified. Gene annotations, gene ontology (GO) enrichment and RNA-seq analyses of the genomic regions of those 7 QTL clusters identified 47 candidate genes for seed-related traits. These genes are highly expressed in seed-related tissues and nodules, which might be deemed as potential candidate genes regulating the seed size, weight and shape traits in soybean. This study provides detailed information on the genetic basis of the studied traits and candidate genes that could be efficiently implemented by soybean breeders for fine mapping and gene cloning, and for MAS targeted at improving these traits individually or concurrently.